EXPECTATION – PERFORMANCE GAP DALAM PEMANFAATAN SPREADSHEET PADA MAHASISWA PENDIDIKAN AKUNTANSI - Hasna Fairuz Rizlahita; Sri Sumaryati (Universitas Sebelas Maret, 2026)
This study aimed to analyze differences between students' perceived expectations and perceived performance in spreadsheet utilization among Accounting Vocational High School (SMK Akuntansi) and Senior High School (SMA) graduates, compare the expectation–performance gap between both groups, and identify perceived contributing factors. A quantitative approach with an ex post facto causal-comparative design was employed. The sample consisted of 157 Accounting Education students at Universitas Sebelas Maret selected using one-stage cluster sampling. Data were collected through a 1–10 numerical scale questionnaire and analyzed using the Wilcoxon Signed Rank Test, Mann–Whitney U Test, and descriptive analysis. Results indicated significant differences between perceived expectations and perceived performance across all spreadsheet competency indicators, with expectations exceeding perceived performance. The largest gap occurred in the reliability and control indicator, followed by assessment and evaluation, and functional competency and modeling. No significant difference was found in the expectation–performance gap between SMA and SMK Accounting graduates. The main perceived contributing factors were course materials and assignments, device availability, motivation to complete assignments, and teaching quality. The study recommends strengthening spreadsheet learning by integrating spreadsheet-based materials and assignments into relevant courses to develop advanced spreadsheet competencies.Keywords: Accounting Education; Expectation-Performance Gap; Perceived Performance; Spreadsheet Skills.